2019
DOI: 10.14202/vetworld.2019.112-118
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and antibody detection of Newcastle disease virus in a neglected society in Nigeria

Abstract: Aim: This study aimed to assess the level of awareness of rural poultry farmers on vaccination and to detect Newcastle disease virus (NDV) antibody in local birds (LB) and eggs in Kwara State, Nigeria. Materials and Methods: Data on farmers' attitude, knowledge, practices, and experiences on ND mortality were obtained through an interview using a structured cross-sectional checklist. NDV antibodies were detected in sera and egg yolks of local chickens (LC) and guinea fowls (GF) using hemagglutination inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…As shown in our work, wild birds were apparently healthy, but a few birds showed ruffled feathers with whitish-green diarrhea, while post-mortem examination showed enteritis, whitish-green intestinal contents, and cloudiness of the air sacs. The present clinical findings are consistent with previous data reporting respiratory, gastrointestinal, circulatory, and nervous signs in infected chickens [ 75 , 76 ]. The clinical signs might vary depending on several factors, such as the pathogenicity of the virus; host factors such as age, species, and immune status; infectious dose duration and extent; and concurrent infections [ 77 ].…”
Section: Discussionsupporting
confidence: 93%
“…As shown in our work, wild birds were apparently healthy, but a few birds showed ruffled feathers with whitish-green diarrhea, while post-mortem examination showed enteritis, whitish-green intestinal contents, and cloudiness of the air sacs. The present clinical findings are consistent with previous data reporting respiratory, gastrointestinal, circulatory, and nervous signs in infected chickens [ 75 , 76 ]. The clinical signs might vary depending on several factors, such as the pathogenicity of the virus; host factors such as age, species, and immune status; infectious dose duration and extent; and concurrent infections [ 77 ].…”
Section: Discussionsupporting
confidence: 93%
“…[ 38 ] have also shown that in Benin, Burkina Faso, Mali, Ghana, and Guinea, ND is the major cause of mortality and morbidity in poultry. Several studies have shown the endemicity of this disease in traditional poultry farming in countries, such as Côte d’Ivoire [ 39 , 40 ], Nigeria [ 41 , 42 ], Sudan [ 43 ], Uganda [ 44 ], Mauritania [ 45 ], Niger [ 46 ], Tanzania [ 47 ], Madagascar [ 48 , 49 ], Togo [ 50 ], and Congo [ 51 ]. This disease, although not the main cause of death in Cameroon [ 52 ], Mali [ 16 ], Burkina Faso [ 53 ], Chad [ 54 ], and Zimbabwe [ 55 ], is the second cause of death accounting for, on average, 35%.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Aboe PAT, et al [95] have also shown that in Benin, Burkina Faso, Mali, Ghana, and Guinea, NDV is the major cause of mortality and morbidity in poultry. Several studies have shown the endemicity of this disease in traditional poultry farming in countries, such as Côte d'Ivoire Couacy-Hymann E, et al [96], Kouakou AV, et al [97], Nigeria Jibril AH, et al [98], Daodu OB, et al [99], Sudan Elmardi NA, et al [100], Uganda Kasozi KI, et al [101], Tanzania Wyatt A, et al [102], Madagascar Rasamoelina-Andriamanivo H, et al…”
Section: After the Classification Of The Virus In The Familymentioning
confidence: 99%